2009
DOI: 10.3171/2008.11.spine0856
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tumor curettage and interstitial delivery of samarium-153 coupled with kyphoplasty for treatment of vertebral metastases

Abstract: Object The object of this study was to investigate the use of a minimally invasive technique for treating metastatic tumors of the vertebral body, aimed at relieving pain, preventing further tumor growth, and minimizing the adverse effects of systemic use of samarium-153 (153Sm). Methods The procedure is performed in the same fashion as a kyphoplasty, using a unilateral extrapedicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Cardoso et al 7 have described the interstitial delivery of samarium-153 coupled with kyphoplasty for the treatment of vertebral metastases. Similar to our technique, they demonstrated that the combined percutaneous debulking of confined vertebral metastases and the delivery of local radiotherapy for tumor control was feasible and safe.…”
mentioning
confidence: 99%
“…Cardoso et al 7 have described the interstitial delivery of samarium-153 coupled with kyphoplasty for the treatment of vertebral metastases. Similar to our technique, they demonstrated that the combined percutaneous debulking of confined vertebral metastases and the delivery of local radiotherapy for tumor control was feasible and safe.…”
mentioning
confidence: 99%
“…Whether metastases in the pedicle can be approached with this technique remains to be determined based on the dose to the spinal cord and the stability of the positioning of the IORT device. External beam radiotherapy or radiosurgery [8,9] even when combined with bisphosphonates do provide improved structural stability only after a prolonged period of time and the hazards of open radionuclides are avoided with this X-ray based approach [10]. A detailed discussion about different fractionation schedules for the treatment of spinal cord metastases can be found in a recent review [11].…”
Section: Discussionmentioning
confidence: 99%
“…Care was taken to prevent perforation of the cortical surfaces of the vertebral body during this step. Details of tumor curettage have been previously reported (17).…”
Section: Methodsmentioning
confidence: 99%